Assembling health rights in global context : genealogies and anthropologies - Mold, Alex.; Reubi, David (Abingdon, Oxon : Routledge, 2013)
'What do we mean when we talk about rights in relation to health? Where does the language of health rights come from, and what are the implications of using such a discourse? During the last 20 years there have been an increasing number of initiatives and efforts for instance in relation to HIV/AIDS which draw on the language, institutions and procedures of human rights in the field of global health. This book explores the historical, cultural and social context of public health activists' increasing use of rights discourse and examines the problems it can entail in practice. Structured around three interlinked themes, this book begins by looking at how and why some health issues came to be framed as human rights issues. It goes on to look at what health as a human right means for our understandings of citizenship and the political landscape. The final part of the book investigates what happens when health rights are put into practice implemented, realised, cited, ignored and resisted. Health Rights in Global Context provides an in-depth discussion of the historical, social and political context of rights in health and develops much needed critical perspectives on the human rights approach to global health. It will be of interest to scholars of public health and human rights within health care as well as sociology and anthropology'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Bioethics -- history; Medical policy -- History